KONSEPTUALISASI TEOLOGI KHAWARIJ VERSUS SYI’AH DALAM PROBLEMATIKA SPIRITUAL PADA DUNIA GEN-Z - Fadhlan Kamali Batubara; Firji Hafiz; Lola Amelia; Muhammad Haris Sulaiman Saragih; Nur Aini; Nazwa Aqilla Lufti Damanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the increasing spiritual problems among Generation Z in the era of digital disruption, characterized by tendencies toward extreme religious attitudes, either in the form of rigid religiosity or shallow emotional spirituality. This research aims to analyze the relevance of Khawarij and Shi’ah theological concepts as a framework to understand such spiritual crises. The research questions focus on the concepts of Khawarij and Shi’ah theology, their comparison, and their relevance to the spiritual issues of Generation Z. This study employs a library research method with a descriptive qualitative approach, using conceptual and comparative analysis. Data were collected from classical and contemporary literature and analyzed through content analysis techniques, including data reduction, presentation, and conclusion drawing. The findings reveal that Khawarij theology represents a rigid, exclusive, and judgmental pattern of religiosity, while Shi’ah theology reflects a pattern based on spiritual authority and emotional depth. In the context of Generation Z, these patterns manifest in modern religious behaviors such as judgmental attitudes on social media and dependency on spiritual figures. Therefore, a moderate approach that integrates moral firmness and spiritual depth is needed to build a balanced, inclusive, and adaptive religious character in facing contemporary challenges.